GOOD ENVIRONMENTAL GOVERNANCE AND SUSTAINABLE DEVELOPMENT: MILLENNIAL EMPOWERMENT STRATEGY THROUGH THE COFFEE SCHOOL PROGRAM - Kagungan D.; Zainal A.A.; Rosalia F. (Russian Journal of Agricultural and Socio-Economic Sciences)
The West Lampung Regency Government, Indonesia, has pioneered a millennial empowerment initiative through the establishment of a coffee school. This program encompasses vocational education in coffee cultivation and processing, designed to enhance both economic and social outcomes. The coffee school, located in Sukajaya Village, not only serves as a training center but also promotes agro-tourism due to its strategic location. The program aligns with sustainable development principles, emphasizing resource preservation for future generations and environmental consciousness. Millennials, known for their adaptability and openness to innovation, are a key focus of this initiative, benefiting from its practical training and entrepreneurial opportunities. The study explores the relationship between good environmental governance, sustainable development, and the empowerment of millennials, particularly through the Coffee School Program, and highlights its potential to improve community welfare and the local coffee industry.